1998
DOI: 10.1002/hep.510280419
|View full text |Cite
|
Sign up to set email alerts
|

Dietary juniper berry oil minimizes hepatic reperfusion injury in the rat

Abstract: Juniper berry oil is rich in 5,11,14-eicosatrienoic acid, a polyunsaturated fatty acid similar to one found in fish oil, yet less prone to peroxidation. Dietary fish oil treatment has been shown to effectively reduce reperfusion injury; therefore, the effects of a diet containing juniper berry oil on hepatic reperfusion injury in a low-flow, reflow reperfusion model were investigated in the rat. Rats were fed semisynthetic diets containing either juniper berry oil, fish oil, or corn oil for 14 to 16 days. Dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The deficiency of PUFA in the diet may increase the hepatic enzymes in serum (Lanari et al, 1999). In this study, serum GOT, GPT and ALT levels in the JBO groups significantly decreased over those in the control group ( p < 0.05); however, no significant change was observed in the LDH value ( p > 0.05), which may have been caused by PUFA contained in the JBO; JBO is believed to support the hepatic tissue due to these PUFA and aromatic components (Jones, Zhong, Enomoto, Schemmer, & Thurman, ). Similarly, Babalola et al () have reported that serum hepatic enzyme level significantly decreased in juvenile vundu ( Heterobranchus longifilis ) fed with feeds containing vegetable oil.…”
Section: Discussionmentioning
confidence: 56%
“…The deficiency of PUFA in the diet may increase the hepatic enzymes in serum (Lanari et al, 1999). In this study, serum GOT, GPT and ALT levels in the JBO groups significantly decreased over those in the control group ( p < 0.05); however, no significant change was observed in the LDH value ( p > 0.05), which may have been caused by PUFA contained in the JBO; JBO is believed to support the hepatic tissue due to these PUFA and aromatic components (Jones, Zhong, Enomoto, Schemmer, & Thurman, ). Similarly, Babalola et al () have reported that serum hepatic enzyme level significantly decreased in juvenile vundu ( Heterobranchus longifilis ) fed with feeds containing vegetable oil.…”
Section: Discussionmentioning
confidence: 56%
“…Conversely, n-3 PUFAs downregulate steroid-responsive element binding protein 1-c, which increases transcription of genes responsible for fatty acid synthesis such as fatty acid synthase and stearoyl Co-A desaturase. 28 Dietary provision of n-3 PUFAs via fish oil modulates the fatty acid composition of cell membrane phospholipids 29 and reduces intrahepatic lipid accumulation as well as the percentage of big fat droplets and therefore improves microcirculation. 20 In ob/ob mice, n-3 PUFA supplementation resulted in conversion of hepatic macrosteatosis to microsteatosis with a change of n-6:n-3 PUFA ratio to approach that of lean livers.…”
Section: Discussionmentioning
confidence: 99%
“…32 Juniper berry oil, which is rich in 5,11,14-eicosatrienoic acid, a polyunsaturated fatty acid similar to one found in fish oil, ameliorated reperfusion injury in rat liver. 29 In contrast, failure of dietary provision with fish oil to attenuate warm I/R injury in rat liver also has been reported. 33 We found remarkable amelioration of microcirculation associated with significantly lower AST release both before ischemia and after reperfusion in the n-3 PUFAsupplemented mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the richest sources of JA is biota seed (Biota orientalis) a well-known source and a very popular component of traditional Chinese pharmacopeia [17]. A number of beneficial properties have been reported for conifer oils containing NMI PUFA including antiinflammatory [18], anti-proliferative and skin protective [19], cholesterol-lowering activity [20,21], suppression of hypertension [22], modulation of immune response [23], enhancement of memory [24][25][26], minimization of hepatic reperfusion injury [27], and anti-proliferative properties [28]. Approaches to JA isolation have included multistep thin layer argentation chromatography, urea inclusion and argentation liquid chromatography in combination with solid phase extraction chromatography, countercurrent chromatography or via chemical synthesis [6,8,[28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%